A systematic review of injecting-related injury and disease among people who inject drugs. (1st February 2017) - Larney, Sarah; Peacock, Amy; Mathers, Bradley M.; Hickman, Matthew; Degenhardt, Louisa
Highlights: Skin and soft tissue infections are common among people who inject drugs. There are few data on other injecting-related injuries and diseases. Cleaning injecting sites and avoiding intramuscular and subcutaneous injecting may reduce injecting-related injury and disease (IRID) risk. Better epidemiological data are needed to inform prevention and care interventions. Abstract: Background: Non-viral injecting-related injuries and diseases (IRID), such as abscesses and vascular damage, can result in significant morbidity and mortality if untreated. There has been no systematic assessment of the prevalence of non-viral IRID among people who inject drugs; this review aimed to address this gap, as well as identify risk factors for experience of specific IRID. Methods: We searched MEDLINE, Embase and CINAHL databases to identify studies on the prevalence of, or risk factors for, IRID directly linked to injecting in samples of people who inject illicit drugs. Results: We included 33 studies: 29 reported IRID prevalence in people who inject drugs, and 17 provided data on IRID risk factors. Skin and soft tissue infections at injecting sites were the most commonly reported IRID, with wide variation in lifetime prevalence (6–69%). Female sex, more frequent injecting, and intramuscular and subcutaneous injecting appear to be associated with skin and soft tissue infections at injecting sites. Cleaning injecting sites was protective against skin infections. Other IRID included infective endocarditis (lifetime prevalence ranging from 0.5–12%); sepsis (2–10%); bone and joint infections (0.5–2%); and thrombosis and emboli (3–27%). Conclusions: There were significant gaps in the data, including a dearth of research on prevalence of IRID in low- and middle-income countries, and potential risk and protective factors for IRID. A consistent approach to measurement, including standardised definitions of IRID, is required for future research.